Analyzing the Effect of Supply Chain Strategies and Collaboration on Performance Improvement Using MIMIC Model - Kunnapapdeelert, Siwaporn; Pitchayadejanant, Krittipat (International Journal of Industrial Engineering and Management, 2021)
The supply chain strategies, lean and agile, are widely discussed in Thai manufacturers. This study investigates the impact of supply chain strategies on integrations and the effect of supply chain integrations on operational performance. Multiple indicator multiple cause model is used for analyzing the data gathered from Thai manufacturers. The results indicated that supply chain strategies are positively associated with all supply chain integrations (supplier integration, customer integration, and internal integration), and internal integration positively impacts operational performance. Also, Thai manufacturers must provide excellent internal integration inside the organization to enhance the integration between suppliers and customers. Article history: Received (April 25, 2021); Revised (July 17, 2021); Accepted (July 27, 2021); Published online (September 10, 2021)